Evidence characterising skills, competencies and policies in advanced practice critical care nursing in Europe: a scoping review protocol - Sara Nordentoft; Anders Larsen; Ingrid Egerod; Gudrun Kaldan; Suzanne Forsyth Herling; Thordis Thomsen (BMJ Open)
Introduction The management of critically ill patients is challenged by increasing population age and prevalence of comorbid diseases. High-quality intensive care nursing practice is imperative to accommodate these issues. The roles of the nurse practitioner (NP) and the acute care NP have existed for decades in the USA, Canada and Australia but are still evolving in Europe. Some European countries have introduced the advanced practice nurse (APN), but the current standard of the advanced level of nursing is variable and consensus regarding the framework, role and definition is lacking. Literature and evidence are sparse as well. Identification of skills and competencies required for the APN is warranted. Mapping skills and competencies will enable future educational harmonisation and facilitate mobility of the advanced-level intensive care nursing workforce across Europe. The aim of our scoping review is to identify literature describing skills, competencies and policies characterising advanced nursing practice in intensive care across Europe.Methods and analysis We will apply a five-stage scoping review methodology with a comprehensive systematic literature search as outlined by Arksey and O’Malley. In collaboration with a research librarian, we will search nine interdisciplinary databases and grey literature for publications originating in European countries in 1992–2018. Using a two-stage screening process with Covidence to remove duplicates, we will first scan the title and abstract and then perform full-text review to determine the eligibility of the papers. Qualitative content analysis will be used to chart the data.Ethics and dissemination Our study is a part of the European Union-funded INACTIC project (International Nursing Advanced Competency-based Training for Intensive Care) with the overall aim of developing a common European curriculum for advanced practice critical care nursing. Results from this scoping review mapping the evidence of APNs in Europe will be presented at national and international conferences and published in a peer-reviewed journal.